Implementation of Information and Comuncation Technology (ICT) into UKI Learning During The Covid-19 Period - Sinaga, Dameria (Universitas Ahmad Dahlan, 2024)
In 2020, around February, the spread of the corona virus disease occurred throughout the world, causing changes in the economic, educational and health sectors. Likewise, in our country, Indonesia, learning has been disrupted by the presence of the corona virus disease, where previously learning was carried out in classrooms, but to prevent the spread of this virus from becoming widespread, learning was not carried out in schools but in individual homes. In order for learning to take place effectively even if you do not meet face to face, learning is carried out online. The results of this research show that using ICT learning is useful in supporting the learning process. By using ICT, teachers can do homework, mid-semester exams, final semester exams and can give grades to students without disturbing them and not being late in the class promotion process. As a result of using ICT, the learning process runs smoothly and effectively, providing motivation and making the learning process easier in getting broader information about learning at UKI. The purpose of this study is to facilitate learning during the COVID-19 period. We know that during the COVID-19 period all learning was carried out at home using daring learning. The study was conducted at the Christian University of Indonesia with a sample of 58 students who were randomly selected. And using the experimental method with a 2 x 2 factorial design.The findings of this study are to make students more active in learning. The results showed that learning through E-Learning can improve learning and competency-based curriculum especially UKI during the COVID-19 period